(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Calculating the modified index of air pollution (I.A.P.) (Kondratyuk, 1996,) for 301 points in the Yalta amphitheatre, a range of meaningsfrom 0 to 87 was obtained. The data was used as the basis for map zoning. Six isotoxical lichen zones were distincted: polluted zone (I.A.P. from 0 to 5), moderately polluted zone (I.A.P. from 6 to 10), slightly polluted zone (I.A.P. from 11 to 20), moderately clean zone (I.A.P. from 21 to 30), background clean zone (I.A.P. from 31 to 40), zoneof high cleanness (I.A.P. from 41 and higher). 134 corticolous lichens have been found in the urbane localities of the Yalta amphitheatre. The polluted zone in the Yalta town is formed by areas with heavy traffic along the streets Sadovaya, Karla Marksa, Marshaka, Moscowskaya, Kievskaya, Ruzvel’ta and Sverdlova with 14 species of lichens found here (0 –5 species per each tree). The moderately polluted zone is adjacent to the pollution zone extending into a town by two sleeves along valleys of the rivers Derekoyka and Vodopadnaya (Uchansu). 27 corticolous lichens were found in this zone. The slightly polluted zone includes three separated localities which covering mostly the urbanized territories of Yalta. The moderately clean zone covers large areas including foot of the hill Darsan and most of parklands. 56 species of corticolous lichens occur in this zone. The background clean zone is mainly located in the north (up from Vinogradne), north-west (Polyana Kazok) and the east (around Otradne) of urbanized ecosystems in the Yalta amphitheatre. 63 lichen species have been found here. The zone of high cleanness is small and comprizes four separated localities in Livadiya, park at the sanatorium “Russia”, on the hill Darsan and in the Nikita region . 107 species of corticolous lichens have been found in this zone. In general, the air quality in urbanized landscape of whole Yalta amphitheatre can be considered moderately clean, but in the town of Yalta, slightly polluted zone prevails.